Investigating isoprenylcysteine carboxyl methyltransferase (ICMT) deficiency on BRAF and NRAS mutated malignant melanoma cell lines - Blell, Josefin (My University, 2018)
Malignant melanoma has the highest increase in incidence out of all cancers forms and the treatments available today all have drawbacks. Knockdown of the gene isoprenylcysteine carboxyl methyltransferase (ICMT) has been shown to reduce cancer growth in both BRAF and NRAS mutated malignant melanoma cell lines, but the mechanism is so far unknown. Unpublished RNA sequencing data by Dalin & Äng et al. reveal that the gene X is significantly upregulated at mRNA level in the investigated cell lines with ICMT deficiency. Gene X is important for a certain signaling pathway, which have been linked to cancer. The connection between ICMT and X were investigated in a literature study focusing on their roles in the signaling pathway. Proliferation and invasion assays were conducted in vitro on ICMT and X deficient cells. With both shRNA and CRISPR/Cas9 transduction, ICMT and X deficient cells were generated as well as the combination of both. The complete absence of the desired proteins in CRISPR/Cas9 treated clones were confirmed with western blot. ICMT knockout cells were confirmed to grow slower than all the other treatments and gene X knockouts also showed reduced proliferation. Interestingly, the combination of both gene X and ICMT knockouts grew faster and invades more than the ICMT and gene X single knockouts did. This strengthens the hypothesis that ICMT and X is connected, and that knockout of both genes leads to a rescue effect on proliferation. In other words, it is shown that X mediates the antiproliferative effect of ICMT. However, the mechanism of how ICMT and X is connected is yet to be discovered.
Keywords: Cellbiologi; Cell- och molekylärbiologi; Medicinsk bioteknologi (med inriktning mot cellbiologi); Livsvetenskaper; Cell Biology; Cell and Molecular Biology; Medical Biotechnology (with a focus on Cell Biology); Life Science